The role of COMT polymorphism in modulation of prefrontal activity during verbal fluency in bipolar disorder - Devrimci-Ozguven, Halise; Hosgoren Alıcı, Y.; Demirbugen Oz, M.; Suzen, H.S.; Kale, H.E.; Baskak, B. (Neuroscience letters, 2020)
•Low Verbal Fluency performance persists in the euthymic phase.•COMT polymorphism was not associated with altered Verbal Fluency performance but associated with frontal activity.•Val/Met individuals exhibit overactivity in left medial and dorsolateral PFC compared to Met/Met individuals with Bipolar disorder.•Only among the Met/Met cases, bipolar subjects displayed higher activity than the controls in left and right lateral edges of the PFC. Verbal fluency (VF) impairment is a strong predictor of social functioning in bipolar disorder (BPD). The enzyme catechol-O- methyltransferase (COMT) has a critical role in cognitive responses by modulating dopaminergic activity in the prefrontal cortex (PFC). Here, we investigated the role of COMT polymorphism (i) in VF performance as well as (ii) in modulation of PFC activity during a VF-task in euthymic BPD patients. 30 subjects with remitted BPD-I and 23 healthy controls (HCs) were genotyped for COMT Val158Met (rs4680) polymorphism and were compared in a VF-task. PFC activity was measured by 24-Channel Functional Near Infrared Spectroscopy. Bipolar subjects displayed lower VF performance than HCs. During the VF-task, BPD-group displayed higher activity than HCs in the Brocca’s area, Premotor-cortex and supplementary motor area (SMA). In the index group, Val/Met polymorphism was associated with higher activity in the left- frontopolar and dorsolateral PFC (DLPFC) during the VF-task. Antipsychotic use may have interfered with the results. Increased activity in the Brocca’s area may represent compensation of low VF performance, whereas hyperactivity in premotor-cortex and SMA may be associated with increased behavioral intention and/or restlessness in BPD. Higher activity in left-frontopolar and DLPC among Val/Met individuals compared to Met-homozygotes may represent less effective prefrontal dopaminergic signaling in Val/Met individuals with BPD.